Online trading: issues and syariah perspective (forex) / Nurfarzana Huda Shahanand … [et al.] - Shahanand, Nurfarzana Huda; Osman, Nur Iylia' Syamimi; Baharudin, Anis Masithah; Mohd Affandy, Nazirah; Zamri, Muhammad Faiz Iqmal (2023)
The forex (foreign exchange) business, or better known as foreign exchange, is currently a business that has quite large and significant influence on society. This is demonstrated by the rise in circulation and activity in the capital market, where daily transaction can reach billions of dollars. Since this business activities can lead their investors became wealthy in short period and generate huge amount of profit, it has become a visually appealing and alluring business model for the majority of people to participate in their business. The forex trading business is included in the category of contemporary Islamic legal issues. As a result, it has the legal status of ijtihadiyyah, which falls under the category of law fi ma la nasha fih (legal concerns lack a clear legal text reference).